Cubical Shape Enhances the Interaction of Layer‐by‐Layer Polymeric Particles with Breast Cancer Cells. Issue 17 (1st October 2015) - Alexander, Jenolyn F.; Kozlovskaya, Veronika; Chen, Jun; Kuncewicz, Thomas; Kharlampieva, Eugenia; Godin, Biana
Abstract : Blood‐borne objects display a nonspherical shape with in‐flow dimensions much larger than the vascular endothelial fenestrations, yet, at the diseased state, are able to traverse through these fenestrations owing to their elasticity. The role of physical parameters including shape and elasticity in the behavior of objects found in the tumor microenvironment needs to be understood to ultimately enhance chemotherapy and minimize its side effects. In this study, sphere‐ and cube‐shaped biocompatible elastic microparticles (EM) made via layer‐by‐layer assembly of hydrogen‐bonded tannic acid/poly( N ‐vinylpyrrolidone) (TA/PVPON) as hollow polymer shells and their rigid core‐shell precursors (RM) are explored. In contrast to rigid five‐bilayer (TA/PVPON) core shells, hollow elastic shells are unrecognized by J774A.1 macrophages, yet interact with endothelial and breast cancer cells. Internalization of cubical shells is fivefold more efficient by HMVEC (human microvascular endothelial cells) and sixfold and 2.5‐fold more efficient by MDA‐MB‐231 and by SUM159 (breast cancer cells), respectively, compared to spherical shells. The interaction of cubical (TA/PVPON)5 shells with endothelial cells is similar under 10 s −1 (characteristic of tumor vasculature) and 100 s −1 shear rate (normal vasculature) while it is decreased at 100 s −1 shear rate for the spherical shells. Our data suggest that cubical geometry promotes interaction of particles with breast cancer cells, while elasticity prevents engulfment by phagocytic cells in the tumor microenvironment. Abstract : Understanding the role of shape and elasticity in the behavior of objects in the tumor microenvironment is crucial for designing more efficient and less toxic therapies. Sphere‐ and cube‐shaped biocompatible elastic microshells and their rigid core‐shell precursors are explored. Cubical particles interact better with breast cancer cells, while elasticity prevents engulfment by the cells of reticulo–endothelial system.